Perilaku Pemilih Warga Desa Golongan Muda dan Golongan Tua dalam Pemilihan Kepala Desa - Jama, Saverinus Rio; Wiyono, Suko; Hady, Nuruddin (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to analyze the portrait, shape, and strengthening of the voting behavior of villagers and the political education of young and old villagers in the election of village heads. This study used a case study qualitative approach with observation, interviews, and documentation as data collection techniques. The results showed that the portrait of villager voting behavior in the village head election was seen through the use of voting rights, material and physical support, and participation in village deliberations. The form of the voting behavior of villagers in the village head election is included in the categories of novice voters, sawing voters, floating masses, and permanent voters. Strengthening the voting behavior of villagers in the election of village heads was carried out through socialization carried out by village officials, contestants, volunteers, churches, and the committee of the voting group. The political education of young villagers in the election of village heads was obtained from various online media, while the older group received political education from print media.